2018
DOI: 10.22456/1679-9216.81809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Halofuginone Lactate and Paromomycin in the Treatment of Calves Naturally Infected with Cryptosporidium parvum

Abstract: Background: Cryptosporidiosis is one of the most important problems among neonatal ruminants. Cryptosporidium parvum is the agent causing the disease. Cryptosporidium infection, responsible for diarrhea, dehydration, weight loss and death in neonatal ruminants, leads to significant economic losses for producers. In calves naturally or experimentally infected with cryptosporidiosis, many agents have been reported to have therapeutic and protective effects. The objective of this study was to compare the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
3
7
0
1
Order By: Relevance
“…Various drug trials have been conducted in the treatment of cryptosporidiosis. Drugs including paro- momycin, toltrazuril, halofuginone, decoquinate, azithromycin, some feed additive and tylosin are used for prophylaxis and treatment of cryptosporidiosis (Paraud & Chartier, 2012;Aydogdu et al, 2018;Yagci et al, 2017;Vélez et al, 2019). Paramomycin is one of the most efficient drugs used against Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various drug trials have been conducted in the treatment of cryptosporidiosis. Drugs including paro- momycin, toltrazuril, halofuginone, decoquinate, azithromycin, some feed additive and tylosin are used for prophylaxis and treatment of cryptosporidiosis (Paraud & Chartier, 2012;Aydogdu et al, 2018;Yagci et al, 2017;Vélez et al, 2019). Paramomycin is one of the most efficient drugs used against Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…infection. The aminoglycoside paromomycin has been found effective in treatment of calves with cryptosporidiosis when administered at a dose of 100 mg/kg/day for seven days (Aydogdu et al 2018). Aminoglycosides are generally known for their nephrotoxic and ototoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of certain drugs may reduce the oocyst excretion and thus probably the environmental pathogen level, the subsequent exposure, and infection of susceptible hosts (Shahiduzzaman and Daugschies, 2012). It has been reported that paromomycin, halofuginone lactate, lasalocid, and sulfaquinoxaline have partial or demonstrable effect against Cryptosporidium in infected neonatal ruminants (Wright and Coop, 2007;Aydogdu et al, 2018). However, knowledge about the treatment of cryptosporidiosis in sheep is limited.…”
Section: Discussionmentioning
confidence: 99%
“…There is no specific treatment for cryptosporidiosis. It has been reported that paromomycin, lasalocid, halofuginone lactate, sulfoxinoxalin, azithromycin and toltrazuril have partial or demonstrable effect against in neonatal ruminants with cryptosporidiosis (Viu et al, 2000;Wright and Coop, 2007;Giadinis et al, 2008;Navarre et al, 2012;Yagci et al, 2017;Aydogdu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Significant results have been found when using halofuginone lactate [93], which is the only one licensed treatment for cryptosporidiosis in calves, thought to interfere with the merozoite and sporozoite stages of Cryptosporidium and proven effective in the control of oocyst shedding [94]. It is an antiprotozoal drug for Eimeria and Theileria, derivative of quinazolinone [95], used both for prevention and treatment [96].…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%